Strategies for Improving Students' Mental and Physical Health Through Sports Curriculum in the Digital Era - Setio Nugroho (Universitas Muhammadiyah Enrekang, 2025)
This study explores the integration of traditional art training and digital literacy as a transformative learning approach in modern education. Conducted in Corawali Village, Panca Lautang District, Sidenreng Rappang Regency, the research focuses on the Sanggar Sastra dan Seni Budaya Masumange, a local art and culture community consisting of 35 active members. The study aims to examine how traditional art practices—such as music, dance, and local crafts—can be revitalized and sustained through the application of digital literacy skills, including multimedia documentation, online promotion, and digital content creation. Using a qualitative descriptive method, data were collected through interviews, observation, and participatory involvement in the community’s art activities. The findings reveal that integrating digital tools into traditional art training not only enhances members’ creativity and technological competence but also strengthens cultural identity and intergenerational knowledge transfer. Moreover, the program fosters community empowerment by enabling members to showcase their art through digital platforms, thereby increasing visibility and potential economic opportunities. The study concludes that combining traditional art education with digital literacy represents an effective strategy for transformative learning, bridging local wisdom with global innovation. This approach can serve as a model for other cultural communities seeking to preserve heritage while adapting to the digital era.